Using Video Self-Modelled Social Stories to Teach Social Skills to a Young Child with Autism. (9th May 2010) - Litras, Stacey; Moore, Dennis W.; Anderson, Angelika
Abstract : The present study investigated the effectiveness of combining Social Stories and Video Self-Modelling (VSM) to teach social skills to a three-year-old child with autism. A multiple-baseline across behaviors design revealed that video self-modelled Social Stories were effective at improving all three target behaviors: greeting, inviting to play, and contingent responding. In addition, these behaviors successfully generalized across settings, toys, and communication partners. Concomitant behavior changes, namely, increased levels of communicative behavior and levels of social engagement were also observed. These results support the effectiveness of video self-modelled Social Stories and illustrate the potential of combined intervention techniques for remedying the social deficits faced by this population.